The The Relationship Of Clean And Healthy Living Behavior To The Risk Of Worms In Children At SD Negeri No 095130 Senio Bangun Mount Malela District Simalungun Regency - Sri Rahma Friani; Pinondang h.siregar; deswidya sukrisna hutauruk; Iin Octaviana Hutagaol (Institute of Computer Science (IOCS), 2021)
The prevalence of helminthiasis in Indonesia based on research is still high, around 60-80% knowing the relationship between clean and healthy living behavior with the risk of helminthiasis in children at State Elementary School Number 095130 SenioBangun. This type of research is analytic. The sample of this study were all students in grades IV, V SD. as much as 37 . The results obtained based on hand washing are known from 37 students the majority of respondents wash their hands well on students who are not at risk as many as 14 respondents (60.9%), based on snack consumption it is known that from 37 students the majority of respondents consume good snacks on risky students as many as 16 respondents ( 76.2%) and based on the use of latrines, it is known from 37 students the majority of respondents use good latrines for students who are not at risk as many as 12 respondents (54.5%). It is hoped that this research can be input for teaching staff and health workers to improve the quality of health services and education as well as information on clean and healthy living behavior by providing counseling.